Development of a Mouse-Adapted Reporter SARS-CoV-2 as a Tool for Two-Photon In Vivo Imaging - Ueki, Hiroshi; Kiso, Maki; Furusawa, Yuri; Iida, Shun; Yamayoshi, Seiya; Nakajima, Noriko; Imai, Masaki; Suzuki, Tadaki; Kawaoka, Yoshihiro (Viruses, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) often causes severe viral pneumonia. Although many studies using mouse models have examined the pathogenicity of SARS-CoV-2, COVID-19 pathogenesis remains poorly understood. In vivo imaging analysis using two-photon excitation microscopy (TPEM) is useful for elucidating the pathology of COVID-19, providing pathological insights that are not available from conventional histological analysis. However, there is no reporter SARS-CoV-2 that demonstrates pathogenicity in C57BL/6 mice and emits sufficient light intensity for two-photon in vivo imaging. Here, we generated a mouse-adapted strain of SARS-CoV-2 (named MASCV2-p25) and demonstrated its efficient replication in the lungs of C57BL/6 mice, causing fatal pneumonia. Histopathologic analysis revealed the severe inflammation and infiltration of immune cells in the lungs of MASCV2-p25-infected C57BL/6 mice, not unlike that observed in COVID-19 patients with severe pneumonia. Subsequently, we generated a mouse-adapted reporter SARS-CoV-2 (named MASCV-Venus-p9) by inserting the fluorescent protein-encoding gene Venus into MASCV2-p25 and sequential lung-to-lung passages in C57BL/6 mice. C57BL/6 mice infected with MASCV2-Venus-p9 exhibited severe pneumonia. In addition, the TPEM of the lungs of the infected C57BL/6J mice showed that the infected cells emitted sufficient levels of fluorescence for easy observation. These findings suggest that MASCV2-Venus-p9 will be useful for two-photon in vivo imaging studies of the pathogenesis of severe COVID-19 pneumonia.